Mesenchymal Stem Cells - Dah-Ching Ding; Woei-Cherng Shyu; Shinn-Zong Lin M.D., Ph.D. (Cell Transplantation, 2011)
Stem cells have two features: the ability to differentiate along different lineages and the ability of self-renewal. Two major types of stem cells have been described, namely, embryonic stem cells and adult stem cells. Embryonic stem cells (ESC) are obtained from the inner cell mass of the blastocyst and are associated with tumorigenesis, and the use of human ESCs involves ethical and legal considerations. The use of adult mesenchymal stem cells is less problematic with regard to these issues. Mesenchymal stem cells (MSCs) are stromal cells that have the ability to self-renew and also exhibit multilineage differentiation. MSCs can be isolated from a variety of tissues, such as umbilical cord, endometrial polyps, menses blood, bone marrow, adipose tissue, etc. This is because the ease of harvest and quantity obtained make these sources most practical for experimental and possible clinical applications. Recently, MSCs have been found in new sources, such as menstrual blood and endometrium. There are likely more sources of MSCs waiting to be discovered, and MSCs may be a good candidate for future experimental or clinical applications. One of the major challenges is to elucidate the mechanisms of differentiation, mobilization, and homing of MSCs, which are highly complex. The multipotent properties of MSCs make them an attractive choice for possible development of clinical applications. Future studies should explore the role of MSCs in differentiation, transplantation, and immune response in various diseases.